Implementation of the Deep Learning Approach in Elementary Schools - Fitri Afrikasari; Enung Hasanah; Dian Hidayati (Global Education Journal, 2025)
The deep learning approach is the latest innovation in the Indonesian education system proposed by the Ministry of Primary and Secondary Education in early 2025. The essence of this approach is to create a learning process that is aware, meaningful, and joyful for students. The purpose of the study is to examine the implementation of deep learning from the way teachers plan, organize, implement, and evaluate deep learning in elementary schools. The research method uses a qualitative method with interview data collection techniques and observation of learning in the classroom. The respondent is an elementary school classroom teacher in the Mantrijeron Yogyakarta Ministry of Education who has implemented deep learning. Thematic data analysis with the help of atlas.ti application 9. The results of the research of elementary school teachers implementing deep learning are still very limited, starting from making a learning plan exactly the same as the example from the ministry, there are no new innovations, learning activities that are just following the directions of the curriculum reference book have not shown creativity independently of the teacher and in terms of organizing students, educators emphasize more on grouping students in learning. A tool to measure the success of deep learning can be done by means of project-based assessments, percentages and self-assessment.